The hills are alive with … Many different folk! Rationalising and operationalising a professional judgment and decision making approach within mountain leadership. Issue 4 (2nd October 2021) - Carson, Howie J.; Davies, Nick; Collins, Loel
ABSTRACT: Growth in the adventure sector has increased the demands on adventure sport professionals. Satisfying a diverse range of participatory motivations, however, requires an adaptable and flexible workforce. In this discursive paper, we suggested that a narrowing of service skills caused by commodification and sportification are compounded by general (mis)perceptions of who best suits the adventure sector. Accordingly, this paper discussed two important implications for outdoor professionals to improve inclusivity standards. Specifically, using mountain leadership as an exemplar, we firstly, presented themes in connection with motivations and social dynamics. Secondly, we contextualised these themes against pertinent environmental challenges. Finally, we presented a decision making approach and its requisite planning and reflective skill-sets, designed to assist mountaineering professionals to negotiate the complexity presented by individualised service provision. We concluded that there are no simple solutions to these complex and multiple issues. Services require better alignment between epistemology and delivery via an epistemological chain.